Content Analysis of Gerindra's Tiktok as a Political Communication Medium For Students of the Faculty of Dakwah and Communication - Abdul Rahman; Winda Kustiawan (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
There is a lack of research on using TikTok by political parties in Indonesia, particularly regarding its impact on university students' political perceptions and participation as the young voter generation. This study analyses the political communication strategies employed by the Gerindra Party through the TikTok platform and its influence on the political perceptions of students at the Faculty of Dakwah and Communication, State Islamic University of North Sumatra. Employing a qualitative case study approach, the research utilises content analysis of Gerindra's TikTok videos and in-depth interviews with students, applying data triangulation to comprehensively understand digital political communication and its effects. The findings indicate that the Gerindra Party employs diverse political communication strategies on TikTok, including informative, persuasive, entertaining, and responsive content to engage a young audience. Prabowo Subianto, as the principal figure, prominently features in the content, with videos lasting 30-60 seconds being the most effective in increasing engagement, averaging 1.2 million views. Content showcasing informal moments of political figures elicited higher responses than formal content. However, TikTok presents limitations in delivering in-depth political issues, and the study also found low digital literacy among students in verifying information. These findings highlight the effectiveness and challenges of digital political communication via TikTok. The study concludes that it is essential to integrate digital citizenship education in higher education institutions to enable students to analyse political content critically, and political parties should develop effective multi-platform communication strategies